Tailoring Participatory Integrated Climate Services for Agriculture (PICSA) for one-health - Ky-Dembele, Catherine; Frimpong-Anin, Kofi; Adomako, Joseph; Yeboah, Stephen; Annan, Rapheal; Embil, Dorothy; Obeng, Elvis Agyei; Martey, Francisca; Bayala, Jules (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
In Ghana, AICCRA is implemented by various institutions and NGOs led by the International Institute for Tropical Agriculture (IITA) Benin. As climate information is key in the process, in collaboration with IITA, the Center for International Forestry Research-World Agroforestry (CIFOR-ICRAF/Sahel) is engaged for capacitating stakeholders for the efficient use of climate information and services through the Participatory and Integrated Climate Services for Agriculture (PICSA) approach. Hence, CIFOR-ICRAF/Sahel) has organized a series of actions including a training of trainers on PICSA approach, and Enhancing National Climate Services (ENACTS) initiative, and various studies to examine the relationship between pest and disease incidence and climatic variability. Findings obtained ought to be utilized for elaborating a module of PICSA one One-health aspect. This is intended to expand the validity scope of PICSA while delivering bundled climate information and one-health advisory services to the farmers in general and vegetable growers in particular. The present working document relates the procedure followed and the lesson learnt.